Deformação piroplástica em porcelanatos - Conserva, Lisandra Rafaela dos Santos (2016)
In recent years porcelain stoneware tiles showed the highest growth in production and consumption in ceramic industry sector. To achieve low porosity, which ensures the high performance of the product, is required the formation of large amount of liquid phases during sintering and the flow of these liquids are responsible for the undesirable pyroplastic deformation. Some factors exacerbate the problem: large and rectangular shapes and faster firing cycles. Moreover, the production of tiles through a more sustainable route, the dry route, lacks studies evaluating the effects of processing method on pyroplastic deformation. Thus, this study aimed to contribute to reducing the incidence of pyroplastic deformations in porcelain stoneware tiles, in order to identify the main variables involved and suggest maneuvers for achieve this goal. In the first stage, technical porcelain stonewares were formulated using common raw materials in this type of manufacturing and prepared by wet route. The main difference between the batches was that 10% of the feldspar was replaced with other raw materials such as potash feldspar and quartz in different granulometries in order to change the characteristics of the liquid phases and to minimize pyroplastic deformation. The characterization of the batches before and after firing, as well the assessment of physical and chemical / mineralogical effects of the raw materials on deformation behavior was essential to identify the variables prevalent in deformation. In second stage some batches from previous step were prepared by dry route method, and then the same tests were performed in order to evaluate the effects of processing route on pyroplastic deformation. The results indicated that batches prepared by dry processing route are less likely to deformation mainly due to heterogeneity of microstructure. In both stages, it was found out that the viscosity of the liquid phase formed during firing is the variable that affects most significantly the pyroplastic deformation of the porcelain obtained by both processing routes studied.